First, we have to find the length of arc AE, knowing that the arc BDA = 180°.
![\begin{gathered} arc(AE)=180-arc(BD)-arc(DE)=180-20-104 \\ \text{arc(AE)}=56 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/spdyu7ugc09pn4uajqihg0mchzidjvd5c9.png)
Then, we use the theorem about the angle formed by two secants, which is equivalent to the semi-sum of the difference between its subtended arcs.
![\begin{gathered} m\angle C=(1)/(2)(AE-BD)=(1)/(2)\cdot(56-20) \\ m\angle C=(1)/(2)\cdot36=18 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/588igwxo413jil5711guwhji3dssvtan34.png)
Therefore, angle C measures 18°.